2019
DOI: 10.3389/fpsyg.2019.01601
|View full text |Cite
|
Sign up to set email alerts
|

Does Really One in Ten Believe Capital Punishment Exists in a Contemporary European Community Country? An Endorsed, Prereviewed, Preregistered Replication Study and Meta-Analysis

Abstract: Background Till et al. (2016) reported that in an Austrian sample approximately one in ten respondents incorrectly believed that Austria still practices, or recently practiced, the death penalty, and that there is a positive association between the amount of weekly television viewing and this gross misperception of the Austrian justice system. Methods An endorsed, prereviewed, preregistered close ( N = 597) served to test the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 25 publications
3
14
2
Order By: Relevance
“…In the current study, we have revised the measure of television viewing and added an additional measure for watching US crime shows based on previous recommendations (Boch et al, 2019). We found that watching US crime shows predicted confusion about the death penalty, which is consistent with a genre-specific cultivation effect (Grabe and Drew, 2007;Bilandzic and Busselle, 2008;Lee and Niederdeppe, 2010).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…In the current study, we have revised the measure of television viewing and added an additional measure for watching US crime shows based on previous recommendations (Boch et al, 2019). We found that watching US crime shows predicted confusion about the death penalty, which is consistent with a genre-specific cultivation effect (Grabe and Drew, 2007;Bilandzic and Busselle, 2008;Lee and Niederdeppe, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, the current study does not provide supporting evidence for an overall across-the-board cultivation effect. The revision of the measures for television viewing in the current study based on recommendations by Boch et al (2019) may have increased their precision and robustness compared to the previous studies. The explicit instruction for respondents to include the use of DVDs, online streaming, and over-thetop media platforms into their estimate for television viewing and US crime show use may explain the differences between the current work and previous studies (Truong, 2011;Till et al, 2016;Boch et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations